Mechanistic analysis of ultrasound-assisted biodiesel synthesis with Cu2O catalyst and mixed oil feedstock using continuous (packed bed) and batch (slurry) reactors. (12th October 2017) - Malani, Ritesh S.; Patil, Shubham; Roy, Kuldeep; Chakma, Sankar; Goyal, Arun; Moholkar, Vijayanand S.
Graphical abstract: Highlights: Statistical optimization of transesterification with Cu2 O catalyst in packed bed reactor. Kinetic analysis of transesterification using model based on Eley-Rideal mechanism. Methanol adsorption on the catalyst is the slowest and rate-limiting step. Sonication enhances reaction kinetics of process but not methanol adsorption on catalyst. Activation energy of the overall process largely contributed by mass transfer steps. Abstract: This paper has investigated the mechanistic issues of ultrasound-assisted transesterification process using solid Cu2 O catalyst and mixed feedstock of non-edible oils. The optimum conditions for transesterification have been determined using statistical experimental design in packed bed catalytic reactor. The kinetic constants of different steps of transesterification process have been determined using kinetic model based on Eley-Rideal mechanism coupled to time profiles of reactants and products of transesterification in batch slurry reactors. The batch experiments have been performed at optimum conditions predicted by statistical experimental design: alcohol/oil molar ratio = 10.6, temperature = 62.5 °C, catalyst concentration = 7.25 wt% oil. It is revealed that adsorption of methanol is the slowest and rate determining step of transesterification process. Sonication enhanced the kinetics of reaction steps of transesterification process, but its effect on methanol adsorption on Cu2 O catalyst was adverse. The activation energy of overall transesterification process was 90.14 kJ/mol; while, the sum total of activation energies of the three reaction steps of triglyceride conversion was 40.98 kJ/mol. These results essentially point to strong mass transfer influence on Cu2 O-catalyzed transesterification process, even in presence of sonication. The adsorptive mass transfer of methanol to catalyst sites is not enhanced by microturbulence generated by sonication. Two probable causes leading to this effect are: discrete and intermittent nature of acoustic (or shock) waves generated by the transient cavitation, and secondly, the high temperature of reaction that offsets the methanol adsorption on catalyst websites.